Strategi Internal Public Relations Dalam Mengkomunikasikan Budaya Perusahaan Di Kompas Tahun 2012 - Lita Try Widya Lestari (2013)

(untitled)
This research is meant to know how is the internal strategy Public Relations in communicating company culture in Kompas. The research methode that is used in this research is quality descriptive. The technique of data collecting is done by interviewing and observing, and the avaible data is litarature study and online browsing. Based on research data which is got through by Determination, Selection and Retention. So it can be said that internal strategy of Public Relations consistently can c